Evaluation of the Heavy Metals Concentration Upon Occupational Workers at Several Petrol Filling Stations in Baghdad City, Iraq - Emran, Faiza Kadhim (Iraqi Journal of Science, 2026)
Several heavy metals emitted from car petrol may accumulate in occupational workers at elevated concentrations, resulting in various impacts on these workers. The current work was designed to assess the blood content of Zn, Cu, and Pb in occupationally exposed workers. Four car filling stations situated within Baghdad city, Iraq, and 40 occupational workers were subjected to this study; in addition, a sample of 20 individuals away from these examined fuel stations was selected to act as a control sample during November 2023. From both occupational workers and control samples, 4 ml of blood from each individual was taken and placed in a gel tube for coagulation. Each blood sample was centrifuged for 40 min at 3000 rpm to separate blood serum. The serum of each sample was placed into glass tubes and kept in a refrigerator at 20º C and then used to assess blood Zn, Cu, and Pb content. Also, the ages of both control and workers samples and the working period of only occupational workers were recorded. The obtained data has shown that the mean of examined blood heavy metals content was significantly lower in the control sample than those detected in occupational workers where control sample had a mean value of Zn of 65.15 ± 11.0, Cu of 101.3 ± 14.57 and Pb of 14.625 ± 2.52 µg/dl while worker sample gave mean value of 98.03 ± 23.07, 123.26 ± 40.96 and 57.68 ±14.33 µg/dl for Zn, Cu, and Pb respectively. Also, this work has found that there were insignificant (P < 0.05) effects of age on blood heavy metals whilst a significant effect of working period (P < 0.001) on blood heavy metal content of examined workers was recorded. Also, t-test analysis has revealed significant differences (P < 0.05) between the mean values of control and occupational workers for all examined blood heavy metals content.